Pemanfaatan Limbah Fly Ash Batubara Untuk Pembuatan Paving Block Geopolimer Dengan Variasi Temperatur Curing Dan Rasio Larutan Aktivator Terhadap Fly Ash - Wasty Rusjaya; Ahmad Fadli; Drastinawati Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Paving blocks used as a construction material for roads, parking area, and city parks. The objectives of this research are to make paving blocks of coal fly ash as a raw material in the manufacturing paving blocks, investigate the effect of curing temperature and the ratio of liquid activator/fly ash on the characteristics of the paving block (compressive strength, porosity, density, crystallinity, and morphology) and testing Toxicity Characteristic Leaching Procedure (TCLP) paving block geopolymer. 247,5 gr of coal fly ash were mixed with 742,5 gr of aggregate (sand) and added 82,88 gr of liquid activator as well as 1,26 gr of superplasticizer inside the container. Then, the mixture was strirred and pour into cube mould with size 5x5x5 cm3, subsequently put at room temperature for 24 hours and dried at a curing temperature of 60 °C, 80 °C, 100 °C. The characteristics of were compressive strength, porosity, density, TCLP, crystallinity, and morphology determined. The result show that increasing curing temperature lead to increasing compressive strength and density while the porosity decreased. The compressive strength, porosity, and density of paving blocks were 19,73-49,33 MPa; 4,0-7,6%; 2,0-2,3 g/cm3; respectively and metal contents Zn, Pb, Cu, Cd were 3,591 mg/L; 1,577 mg/L; 1,079 mg/L; and 0,223 mg/L; respectively. The highes of compressive strength 49,33 MPa was obtained at paving blocks paper at the curing temperature of 100 °C and the ratio of liquid activator/fly ash of 0,7.Keywords: curing temperature; fly ash; geopolymer; paving block; liquid activator